2010
DOI: 10.1007/s13238-010-0083-1
|View full text |Cite
|
Sign up to set email alerts
|

RNF152, a novel lysosome localized E3 ligase with pro-apoptotic activities

Abstract: RING finger protein 152 (RNF152) is a novel RING finger protein and has not been well characterized. We report here that RNF152 is a canonical RING finger protein and has E3 ligase activity. It is polyubiqitinated partly through Lys-48-linked ubiquitin chains in vivo and this phenomenon is dependent on its RING finger domain and transmembrane domain. RNF152 is localized in lysosomes and co-localized with LAMP3, a lysosome marker. Moreover, over-expression of RNF152 in Hela cells induces apoptosis. These result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 26 publications
4
30
0
Order By: Relevance
“…Ring finger protein 152 (RNF152) is an E3 ubiquitin ligase with a RING domain and a transmembrane (TM) domain. Previous studies have suggested that RNF152 promotes apoptosis [18] and negatively regulates mTORC1 signaling by mediating K63-linked polyubiquitination of RagA [19]. In this study, we demonstrate that RNF152 positively regulates TLR/IL-1R-mediated inflammatory response by facilitating oligomerization of MyD88, which subsequently promotes the assembly of Myddosome.…”
Section: Introductionsupporting
confidence: 62%
“…Ring finger protein 152 (RNF152) is an E3 ubiquitin ligase with a RING domain and a transmembrane (TM) domain. Previous studies have suggested that RNF152 promotes apoptosis [18] and negatively regulates mTORC1 signaling by mediating K63-linked polyubiquitination of RagA [19]. In this study, we demonstrate that RNF152 positively regulates TLR/IL-1R-mediated inflammatory response by facilitating oligomerization of MyD88, which subsequently promotes the assembly of Myddosome.…”
Section: Introductionsupporting
confidence: 62%
“…For example, a protein conjugated to a polyubiquitin chain by ubiquitin lysine 48 (but possibly by all non-lysine 63 linkage) is targeted to the 26S proteasome to be degraded [ 80 ]. In our microarray results, one E3 ubiquitin-protein ligase mediating 'Lys–48'-linked polyubiquitination of target proteins (RING finger protein 152 (RNF152)) [ 82 ] was up-regulated in FW ionocytes. Furthermore, two non-ATPase regulatory subunits of the 26S proteasome were concomitantly more expressed (PSMD5 and PSMD 7).…”
Section: Resultsmentioning
confidence: 99%
“…In the human ewing sarcoma cell line, PRKCD could activate mTOR through phosphorylation and inactivation of TSC2 [103], while the TOR pathway has been identified to be a regulator of the cell apoptosis and autophagy in chicken small intestines induced by arsenic [104] and a key player linking specific extracellular milieu and intracellular metabolism during Salmonella infection in chicken [105]. The downregulated ring finger protein 152 (RNF152) predicted to be regulated by the putative downregulated lncRNA NONGGAT004163.2 was localized in lysosomes and could prompt apoptosis of Hela cells [106]. In addition, 1453 mRNAs were also predicted to be trans-regulated by 87 lncRNAs.…”
Section: Discussionmentioning
confidence: 99%